2021
DOI: 10.3390/nu13072476
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bergamot Polyphenols on Mitochondrial Dysfunction and Sarcoplasmic Reticulum Stress in Diabetic Cardiomyopathy

Abstract: Cardiovascular disease is the leading cause of death and disability in the Western world. In order to safeguard the structure and the functionality of the myocardium, it is extremely important to adequately support the cardiomyocytes. Two cellular organelles of cardiomyocytes are essential for cell survival and to ensure proper functioning of the myocardium: mitochondria and the sarcoplasmic reticulum. Mitochondria are responsible for the energy metabolism of the myocardium, and regulate the processes that can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 190 publications
(231 reference statements)
0
22
0
Order By: Relevance
“…Indeed, in a study of 11 overweight-to-obese male patients with T2DM, 12-weeks of progressive endurance/strength training was effective in improving insulin sensitivity, LVEF, cardiac index, and cardiac output, with no variation in cardiac lipid content [ 60 ]. A Mediterranean dietary pattern characterized by a high proportion of mono and polyunsaturated fat, a small portion of red meat, and high quantities of olive oil has demonstrated many cardiovascular benefits, by decreasing inflammatory status, and improving lipid profile, endothelial dysfunction, and insulin sensitivity [ 61 , 62 ]. In particular, in a recent observational study on 9316 men and 27,645 women, including also people with diabetes, a higher adherence to a Mediterranean-style diet evaluated by modified Mediterranean Diet Scores (mMDS) was associated with a 12% reduced risk of HF in men but not in women [ 63 ].…”
Section: Lifestyle Changesmentioning
confidence: 99%
“…Indeed, in a study of 11 overweight-to-obese male patients with T2DM, 12-weeks of progressive endurance/strength training was effective in improving insulin sensitivity, LVEF, cardiac index, and cardiac output, with no variation in cardiac lipid content [ 60 ]. A Mediterranean dietary pattern characterized by a high proportion of mono and polyunsaturated fat, a small portion of red meat, and high quantities of olive oil has demonstrated many cardiovascular benefits, by decreasing inflammatory status, and improving lipid profile, endothelial dysfunction, and insulin sensitivity [ 61 , 62 ]. In particular, in a recent observational study on 9316 men and 27,645 women, including also people with diabetes, a higher adherence to a Mediterranean-style diet evaluated by modified Mediterranean Diet Scores (mMDS) was associated with a 12% reduced risk of HF in men but not in women [ 63 ].…”
Section: Lifestyle Changesmentioning
confidence: 99%
“…The Mediterranean diet (Md), defined as part of the "intangible cultural heritage of humanity," is related to an improvement in health, especially in regard to the reduced incidence of cancer, diabetes mellitus, and, even more significantly, coronary heart disease in the region of Southern Italy [16]. In particular, the reduced intake of red meat alongside the greater consumption of olive oil and plant-based foods means that Md positively affects the onset and progression of heart disease [16].…”
Section: Introductionmentioning
confidence: 99%
“…The Mediterranean diet (Md), defined as part of the "intangible cultural heritage of humanity," is related to an improvement in health, especially in regard to the reduced incidence of cancer, diabetes mellitus, and, even more significantly, coronary heart disease in the region of Southern Italy [16]. In particular, the reduced intake of red meat alongside the greater consumption of olive oil and plant-based foods means that Md positively affects the onset and progression of heart disease [16]. In this context, bergamot (Citrus bergamia Risso et Poiteau) is inserted, a plant endemic to the Calabrian Ionian coast in Southern Italy, a place where the soil and microclimate give the bergamot fruit its peculiar organoleptic characteristics [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter promotes protein nitration contributing to endothelial dysfunction and cell death [ 72 , 73 ]. The pathologies in which the availability of NO is altered, and which determine a harmful impact on the endothelium, through the mechanism described are multiple and include not only metabolic disorders (hyperglycemia, hyperlipidemia, hypertension) [ 74 , 75 ], but also prolonged exposure to drugs, aging and mental disorders [ 76 , 77 , 78 , 79 ]. To date, it is known that oxidative stress favors the extravasation of leukocytes: indeed, some scientific studies have shown that the exposure of Human Umbilical Vein Endothelial Cells (HUVECs) with hydrogen peroxide for 1 h, involves the translocation of selectin P on the cell surface, thus increasing the adhesion of neutrophils [ 53 , 80 ].…”
Section: Introductionmentioning
confidence: 99%